2021
DOI: 10.3389/fneur.2021.697348
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy in Isolated Occlusion of the Proximal Posterior Cerebral Artery

Abstract: Introduction: Endovascular therapy (EVT) is established as first-line treatment for acute ischemic stroke (AIS) due to large vessel occlusion (LVO) in the anterior circulation. For basilar artery occlusion, recent randomized clinical trials demonstrated not only equipoise but also advantages for EVT under particular circumstances. It remains unclear whether EVT offers an advantage over best medical management (BMM) including thrombolysis (IVT) in isolated occlusion of the proximal posterior cerebral artery (PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 16 publications
6
54
1
Order By: Relevance
“…Twelve studies were included in the analysis [5, 12–16, 18, 19, 21, 25, 26, 29]. The search strategy is shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twelve studies were included in the analysis [5, 12–16, 18, 19, 21, 25, 26, 29]. The search strategy is shown in Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EVT is increasingly used to treat patients with isolated occlusions of the PCA. Several recent studies demonstrated the feasibility and safety of EVT in these patients [5,[12][13][14][15][16][17][18][19][20][21]. However, randomized clinical trials demonstrating the efficacy of EVT in the treatment of isolated PCA occlusions are lacking.…”
Section: Although Clinical Symptoms Of Pca Infarcts May Results In a Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…Good outcomes were observed in 59‒66% of all patients at 90 days after EVT ( 16 18 ). Memon et al ( 16 ) and Herweh et al ( 19 ) presented the results of studies of 15 and 23 patients with isolated PPCA occlusion, respectively, who were treated with EVT. The successful recanalization rates were 80% and 54%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical thrombectomy is safe and effective and should be considered in patients presenting with isolated hemianopsia due to acute posterior cerebral artery occlusion. 5 Although the small diameter of the central retinal artery precludes mechanical thrombectomy in patients with CRAO, treatment with intra-arterial tPA may be a consideration if patients with CRAO are not eligible or have contraindications for IV tPA and present in specialized centers within 6 hours of visual loss. 4…”
mentioning
confidence: 99%